2009
DOI: 10.1007/s00439-009-0649-2
|View full text |Cite
|
Sign up to set email alerts
|

African ancestry is associated with risk of asthma and high total serum IgE in a population from the Caribbean Coast of Colombia

Abstract: African descended populations exhibit an increased prevalence of asthma and allergies compared to Europeans. One approach to distinguish between environmental and genetic explanations for this difference is to study relationships of asthma risk to individual admixture. We aimed to determine the admixture proportions of a case-control sample from the Caribbean Coast of Colombia currently participating in genetic studies for asthma, and to test for population stratification and association between African ancest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 70 publications
10
66
1
4
Order By: Relevance
“…[7][8][9][10][11][12][13] In a recent study of 5,493 Hispanic children and adults (including Puerto Ricans), each 20% increment in African ancestry increased the odds of asthma by 40% (95% CI, 1.14-1.72; P ¼ .001). 8 Similar associations have been demonstrated in African American, Colombian, and Brazilian adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10][11][12][13] In a recent study of 5,493 Hispanic children and adults (including Puerto Ricans), each 20% increment in African ancestry increased the odds of asthma by 40% (95% CI, 1.14-1.72; P ¼ .001). 8 Similar associations have been demonstrated in African American, Colombian, and Brazilian adults.…”
Section: Discussionmentioning
confidence: 99%
“…8 Similar associations have been demonstrated in African American, Colombian, and Brazilian adults. [9][10][11] For example, each 10% increment in African ancestry was associated with a 16% increment in the odds of asthma in a case-control study of 796 African American adults (95% CI, 1.06-1.28; P ¼ .002). 11 African ancestry has been associated with higher total or allergen-specific IgEs in some but not all previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The concepts of race and ethnicity include connotations that reflect culture, history, socioeconomics, linguistics, and political status, although race has been considered to be characterized by the primary continent of origin. 17 -20 Recent studies that assess the relationship of self-reported race and genetic ancestry with allergic sensitization in a non-Latino population provide conflicting data about the importance of the use of race/ethnicity; in one study, selfreported African American race was associated with allergic sensitization, asthma, and high total serum immunoglobulin E (IgE) levels, 21 whereas in another study, the association with allergic sensitization was not significant after researchers accounted for the location of residence. 22 The study of genetics is even more complex and difficult when the study population is admixed, that is, contains race and ethnic mixtures.…”
Section: Complexity Of Studying Genetics Race and Ethnicity And Heamentioning
confidence: 99%
“…Delta (δ) values for each of the 15 STR loci were also computed (Listman et al, 2007) for the grouped East versus West African collections to ascertain marker information content, i.e., the ability of the Identifiler loci to differentiate between the two groups of populations. Any locus yielding a δ value ≥ 0.30 (Vergara et al, 2009) is considered informative for discriminating between the two sources.…”
Section: Statistical and Phylogenetic Analysesmentioning
confidence: 99%